Criminologists in the media: a study of newsmaking - Wood, Mark A. (Routledge studies in crime, media and popular culture, 2022)
Introduction -- 1. Public criminology: debates and challenges -- 2. Methodology -- 3. Newsmaking criminology in the post-broadcast era -- 4. The situational logics of newsmaking -- 5. Digital public criminology -- Conclusion.